2001
DOI: 10.2307/3345868
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Modeling and Tempo Patterns as Practice Techniques on the Performance of High School Instrumentalists

Abstract: The purpose of this study was to examine the effect of modeling conditions and tempo patterns on the performance of high school instrumentalists. The independent variables of this study were (a) model versus no model and (b) steady increase of tempo versus performance speed tempo versus alternating (slower and faster) tempos. Subjects (N = 60) were high school wind instrumentalists from the American Midwest and South. Subjects sight-read an étude and then practiced the same étude six times using one of six pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(74 citation statements)
references
References 12 publications
2
71
1
Order By: Relevance
“…In another study that involved the use of practice tapes with high school instrumentalists, Henley (2001) determined that the students who used modeling tapes were better at learning rhythms and mastering tempo, but results about pitch discrimination were inconclusive.…”
Section: Categories Of Practicementioning
confidence: 99%
See 3 more Smart Citations
“…In another study that involved the use of practice tapes with high school instrumentalists, Henley (2001) determined that the students who used modeling tapes were better at learning rhythms and mastering tempo, but results about pitch discrimination were inconclusive.…”
Section: Categories Of Practicementioning
confidence: 99%
“…Instructors reported using their singing voice as a model more often than assigning model recordings or listening to models during lessons. Most of the prior research on modeling is concentrated on the use of model recordings to improve performance achievement (Henley, 2001;Linklater, 1997;Puopolo, 1971;Rosenthal et al, 1988;Zurcher, 1975) rather than live modeling (i.e., voice instructors modeling with their own singing voice). Because these instructors claimed to use this strategy for modeling most often, more research is needed in order to determine the impact it has on the success of singers.…”
Section: Structured Practicementioning
confidence: 99%
See 2 more Smart Citations
“…A study by Henley (2001) identified two approaches that could be used constructively in ensemble performance, and his findings could be applied directly to practice techniques. This study involved six ensembles, each with their own combination of two conditions.…”
Section: Rehearsal Techniques Can Provide Learning Tools For Studentsmentioning
confidence: 99%